Multilayer 3D Chiral Folding Polymers and Their Asymmetric Catalytic Assembly - Yao Tang; Shengzhou Jin; Sai Zhang; Guan-Zhao Wu; Jia-Yin Wang; Ting Xu; Yu Wang; Daniel Unruh; Kazimierz Surowiec; Yanzhang Ma; Shiren Wang; Courtney Katz; et al. (Research, 2022)
A novel class of polymers and oligomers of chiral folding chirality has been designed and synthesized, showing structurally compacted triple-column/multiple-layer frameworks. Both uniformed and differentiated aromatic chromophoric units were successfully constructed between naphthyl piers of this framework. Screening monomers, catalysts, and catalytic systems led to the success of asymmetric catalytic Suzuki-Miyaura polycouplings. Enantio- and diastereochemistry were unambiguously determined by X-ray structural analysis and concurrently by comparison with a similar asymmetric induction by the same catalyst in the asymmetric synthesis of a chiral three-layered product. The resulting chiral polymers exhibit intense fluorescence activity in a solid form and solution under specific wavelength irradiation.